REVIEW OF ACO ALGORITHM ON NETWORK AND SCHEDULING PROBLEM - Almaalei, Nabeel Naeem Hasan; Razali, Siti Noor Asyikin Mohd (Compusoft: an international journal of advanced computer technology, 2019)
The ant colony optimization algorithm is based on the behaviour of real ants. This algorithm was introduced in the 1990s with the aim of finding solutions to problems which simulates the decision-making processes through the use of ants artificial. This paper provides an overview of some of the previous studies and research progress on the traditional and specialized applications of the ACO algorithm towards scheduling and network problems, such as oil pipelines, water distribution system, and natural gas pipelines.